Adult polyglucosan body disease: an acute presentation leading to unmasking of this rare disorder. Issue 3 (27th May 2022) - Johal, Jaspreet; Castro Apolo, Ramiro; Johnson, Michael W.; Persch, Michael R.; Edwards, Adam; Varade, Preet; Yacoub, Hussam
ABSTRACT: Introduction: Adult polyglucosan body disease (APBD) is an autosomal recessive leukodystrophy caused by abnormal intracellular accumulation of glycogen byproducts. This disorder is linked to a deficiency in glycogen branching enzyme-1 (GBE-1). Neurologic manifestations include upper and lower motor neuron signs, dementia, and peripheral neuropathy. APBD is typically a progressive disease. In this report, we discuss a novel case of APBD in a patient who had a sudden onset of spastic quadriparesis preceded by gradual difficulty with gait. Genetic and postmortem analysis confirmed the diagnosis of APBD. Case report: A 65-year-old man was evaluated for a new-onset of spastic quadriparesis, right-gaze preference, and left-sided beat nystagmus. Magnetic resonance imaging (MRI) of the brain revealed areas of white matter hyperintensities most prominent in the brainstem and periventricular regions. MRI of the cervical spine showed marked cord atrophy. Laboratory workup and cerebrospinal fluid analysis were unremarkable. Genetic testing supported the diagnosis of APBD due to GBE-1 deficiency. Postmortem analysis showed multiple white matter abnormalities suggestive of a leukodystrophy syndrome, and histopathologic testing revealed abnormal accumulation of polyglucosan bodies in samples from the patient's central nervous system supporting the diagnosis of APBD. Conclusion: APBD is a rare disorder that can affect the nervous system. The diagnosis can be confirmed with a combination of genetic testing and pathologic analysis of affected brain tissue.